Advances in speech and language technologies for Iberian Languages : third International Conference, IberSPEECH 2016, Lisbon, Portugal, November 23-25, 2016, Proceedings /: third International Conference, IberSPEECH 2016, Lisbon, Portugal, November 23-25, 2016, Proceedings. (2016) - Unknown
No abstract available